MANAJEMEN PESERTA DIDIK UNTUK PENINGKATAN MUTU SANTRI DI MA'HAD DARUL ILMI MADRASAH ALIYAH NEGERI 2 KOTA KEDIRI - Examaya, Fismarada Agvi (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
The many cases that occur with millennial children today include corruption, sexual crimes, obscenity, bullying, drugs and fights between students which cause a person's quality to be low. The existence of a student management process is one of Ma'had's efforts to create quality students in the cognitive, affective and skills fields so that they can be applied in the home, school and community environments. It is hoped that Ma'had's role will be to shape the quality of students through the student management process. The focus of this research is: 1) What is the student management process to improve the quality of santri at Ma'had Darul Ilmi Madrasah Aliyah Negeri 2 Kediri City, 2) What are the results of efforts to improve the quality of santri at Ma'had Darul Ilmi Madrasah Aliyah Negeri 2 Kediri City . This research uses a descriptive qualitative approach with a field study type of research, the informants used are school principals, ma'had supervisors, and ma'had caregivers. Data collection was carried out using observation, interviews and documentation methods. Meanwhile, the analysis was carried out using qualitative analysis in the form of data reduction, data presentation and drawing conclusions. This research produces that, 1) The student management process consists of input, process and output. Input is planning, namely planning the recruitment of students and caregivers. This process includes providing ma'had, habituation and education programs. 2) The results of efforts to improve the quality of students can be called output which can be demonstrated through the various achievements they have made.